Improper wound treatment and delay of rabies post-exposure prophylaxis of animal bite victims in China: Prevalence and determinants. - Qiaoyan Liu; Xiaojun Wang; Bing Liu; Yanhong Gong; Naomie Mkandawire; Wenzhen Li; Wenning Fu; Liqing Li; Yong Gan; Jun Shi; Bin Shi; Junan Liu; et al. (Public Library of Science (PLoS), 2017)
Rabies is invariably a fatal disease. Appropriate wound treatment and prompt rabies post-exposure prophylaxis (PEP) are of great importance to rabies prevention. The objective of this study was to investigate the prevalence and influencing factors of improper wound treatment and delay of rabies PEP after an animal bite in Wuhan, China.This cross-sectional study was conducted among animal bite victims visiting rabies prevention clinics (RPCs). We selected respondents by a multistage sampling technique. A face-to-face interview was conducted to investigate whether the wound was treated properly and the time disparity between injury and attendance to the RPCs. Determinants of improper wound treatment and delay of rabies PEP were identified by a stepwise multivariate logistic regression analysis.In total, 1,015 animal bite victims (564 women and 451 men) responded to the questionnaire, and the response rate was 93.98%. Overall, 81.2% of animal bite victims treated their wounds improperly after suspected rabies exposure, and 35.3% of animal bite victims delayed the initiation of PEP. Males (OR = 1.871, 95% CI: 1.318-2.656), residents without college education (OR = 1.698, 95% CI: 1.203-2.396), participants liking to play with animals (OR = 1.554, 95% CI: 1.089-2.216), and people who knew the fatality of rabies (OR = 1.577, 95% CI: 1.096-2.270), were more likely to treat wounds improperly after an animal bite. Patients aged 15-44 years (OR = 2.324, 95% CI: 1.457-3.707), who were bitten or scratched by a domestic animal (OR = 1.696, 95% CI: 1.103-2.608) and people who knew the incubation period of rabies (OR = 1.844, 95% CI: 1.279-2.659) were inclined to delay the initiation of PEP.Our investigation shows that improper wound treatment and delayed PEP is common among animal bite victims, although RPCs is in close proximity and PEP is affordable. The lack of knowledge and poor awareness might be the main reason for improper PEP. Educational programs and awareness raising campaigns should be a priority to prevent rabies, especially targeting males, the less educated and those aged 15-44 years.